2019
DOI: 10.3390/ijerph16091588
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Improve the Transformation Success Rate of Research Results in the Pharmaceutical Industry? The Game Theoretic Model of Technology Transfer Subjects

Abstract: University–industry technology transfer (UITT) plays an important role in the construction of the national pharmaceutical innovation system. The speculations of a faculty inventor may hinder the successful transfer of pharmaceutical research results. This paper divides the specific process of the transformation of pharmaceutical research results into two parts: (1) an evolutionary game between faculty inventors and universities; and (2) a Stackelberg game between faculty inventors and pharmaceutical companies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Research on technology transfer also encompasses various areas such as diseases, medicine, and pharmacy [52][53][54][55][56][57][58][59][60][61]. There are relatively fewer publications on the methodology for evaluating technology transfer [62][63][64][65]. Efficient technology transfer in the value chain can be crucial in the diffusion of new innovations and technology-associated knowledge [66].…”
Section: Technology Transfer Landscapementioning
confidence: 99%
“…Research on technology transfer also encompasses various areas such as diseases, medicine, and pharmacy [52][53][54][55][56][57][58][59][60][61]. There are relatively fewer publications on the methodology for evaluating technology transfer [62][63][64][65]. Efficient technology transfer in the value chain can be crucial in the diffusion of new innovations and technology-associated knowledge [66].…”
Section: Technology Transfer Landscapementioning
confidence: 99%
“…Friedman [39] argued that evolutionary game theory overcame the limitations of traditional games based on the complete rational hypothesis and had great application prospects in the economic field. Therefore, it was closer to reality when studying the safety regulation of chemical enterprises [40][41][42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the realm of pharmaceutical and life sciences, university technology transfer (UTT) refers to the process of knowledge spillover and valorization, with the objective of translating university-based technology and knowledge into products and services (Bradley et al, 2013;Siegel et al, 2003;Sun et al, 2019). Numerous UTT models and methods have been reported in previous literature, which encompasses, among others, spillover of transitional research findings, incubation of entrepreneurship-related intellectual properties, and creation of commercial products and practical applications (Boh et al, 2016;Cunningham et al, 2019;Grimpe & Fier, 2010;Siegel et al, 2003).…”
Section: University Technology Transfermentioning
confidence: 99%
“…The process of UTT is complex and entails a variety of requirements and dynamics (Sun et al, 2019;York & Ahn, 2012). In the scientific phase in the universities, Triulzi et al (2014) demonstrated that adequate funding is pivotal in motivating universities to generate new scientific knowledge, which can subsequently spill over into the regional societal-industrial ecosystem through various modes of technology transfer.…”
Section: University Technology Transfermentioning
confidence: 99%